(untitled) (ModaPalavra e-periódico, 2018)
The present paper intends to discuss the development and consolidation process of Trend Studies, as a transversal area with transdisciplinary characteristics that was developed in connection with the concepts and practices of areas such as Cultural Studies. The numerous perspectives of Trend Studies and their different associations promoted a dispersed development that should be considered and deconstructed by means of finding common points and practices, or different perspectives, to generate a greater cohesion of concepts and methodologies. In this sense, it is important to present a model for the purpose of systematic identification and observation of trends. The result can generate a parallel process of cultural analysis capable of contributing to a basis for the generation of strategic solutions for institutional and social problems, in a new approach to culture management.